Incompleteness: landscapes, cartographies, citizenships. (17th February 2022) - Wall, Ed
ABSTRACT: Landscapes as dynamic relations between people and worlds are always incomplete. They are partial understandings, evolving knowledges, edited images and unfinished stories of our designed and undesigned environments. Gaps within and between landscapes can reveal histories omitted and individuals silenced, but this open-endedness of landscapes can also provide opportunities to contribute and participate. In this paper I explore how landscapes are always under construction and I argue that their incompleteness offers potential for new practices. I question, how traditions of mapping can reflect dynamic realities of landscapes; how design and representational practices that attempt to fix time and complete space can work with incompleteness; and how designers and researchers can embrace such landscapes as open-ended, collective endeavours. In this paper, I discuss a mapping project called 'Incomplete Cartographies'—an experiment with in-progress cartographies, incrementally informed by situated narratives, and producing new forms of belonging.